Pengembangan Media Pembelajaran Berbasis Google Sites pada Mata Kuliah Semiotika di STKIP Paris Barantai: Development of Google Sites-Based Learning Media in Semiotics Course at STKIP Paris Barantai - Yahya, Andi Muhammad; Noortyani, Rusma; Santanapurba, Harja (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The purpose of developing learning media based on Google Sites in the Semiotics course at STKIP Paris Barantai is to improve the quality of learning by utilizing technology that is easily accessible to students. This research uses a research and development (R&D) method with the ADDIE model, which consists of five stages: (Analysis, Design, Development, Implementation, and Evaluation). As a result of the analysis stage, STKIP Paris Barantai has adequate facilities, but its utilization in learning is still limited. Google Sites-based learning media for the Semiotics course was developed based on the results of design and development. The trial with a small group of 8 students got results (93%) and a large group of 35 students got results (89%) indicating that this learning media is very feasible to use at the implementation stage. The results of the feasibility test conducted by media experts and material experts on Google Sites-based learning media showed that media experts gave an assessment of 85% with a very feasible category, and media experts gave an assessment of 87% with a very feasible category. Based on these results, shows that the use of Google Sites as a learning tool is very effective in improving students' understanding of the material and making education more flexible and interactive. It is hoped that these tools can be an alternative to more advanced learning.